Practices For Planning and Operating Multisite Network Environments Under Crisis Conditions - Alexander Andreyev (Emerging Frontiers Library for The American Journal of Engineering and Technology, 2025)
This paper provides a systematic approach to planning and operating multisite network environments in the face of economic, natural, and cyber crises. The goal of the study is to identify methodological approaches and technological solutions that ensure maintaining business processes via a geo‑distributed network and synthesize them. This includes RTO and RPO requirements and topologies (active–active, active–passive, geo‑distributed clusters) definition as well as a hybrid‑cloud scenario economic feasibility assessment. The relevance of this work is grounded in the increasing sensitivity of the digital economy to downtime, rising cyber risks, and socio-economic shocks (such as migration waves and climate catastrophes), which demand strategic responses to multidimensional threats based on distributed infrastructure and international standards. The novelty of the research lies in a comprehensive content analysis of 18 sources—from reports by Uptime Intelligence, IBM, and UNHCR to the ISO 22301, DORA, NIST SP 800‑34, and ISO/IEC 27001 regulations. A cascading approach to calculating RTO/RPO involves criticality classification of services, dependency modeling, regular drill-over tests, and the development of financial justifications for CAPEX and OPEX flows under TCO and risk bonus. Key findings show that with multisite architecture plus a hybrid cloud, resilience to failures is ensured by automatic failover, regular DRP/BCP testing in operation monitoring MTTR/MTBF continuous error‑budget management; international standards integration resulting in exhaustive checklists for Business Impact Analysis and verification of target metrics; SOAR automation application plus predictive maintenance which mitigates staff shortage problem speeding up recovery; network segmentation and multilayer encryption inside Zero‑Trust framework. This article will be of use to IT infrastructure managers, network system architects, and specialists in business continuity and information security.